2020
DOI: 10.1038/s41598-020-64303-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-range Regulation of Partially Folded Amyloidogenic Peptides

Abstract: neurodegeneration involves abnormal aggregation of intrinsically disordered amyloidogenic peptides (iDps), usually mediated by hydrophobic protein-protein interactions. there is mounting evidence that formation of α-helical intermediates is an early event during self-assembly of amyloid-β42 (Aβ42) and α-synuclein (αS) iDps in Alzheimer's and parkinson's disease pathogenesis, respectively. However, the driving force behind on-pathway molecular assembly of partially folded helical monomers into helical oligomers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 103 publications
0
12
0
Order By: Relevance
“…The 140-residue long α-synuclein monomer consists of three domains: (i) an amphipathic N-terminal region (residues 1–60), where most disease-causing familial mutations are located and which binds to membranes; (ii) a hydrophobic nonamyloid-β component (NAC) region (residues 61–95) that is thought to be the core region for aggregation; and (iii) a disordered negatively charged C-terminal region (residues 96–140). Both N- and C-terminal regions can affect α-synuclein aggregation and fibril propagation. While the negatively charged C-terminal region plays a crucial role in suppressing α-synuclein aggregation, N-terminal residues are essential for fibril formation. , A helix-rich model of the α-synuclein monomer structure has been resolved by solution NMR in the micellar environment and is deposited in the Protein Data Bank (PDB) under PDB ID: 1XQ8 . Using molecular dynamics simulations we study how SK9 interacts with α-synuclein and whether SK9 changes the conformational ensemble of the monomer, potentially modifying oligomerization and hastening the formation of a critical nucleus for seeding fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…The 140-residue long α-synuclein monomer consists of three domains: (i) an amphipathic N-terminal region (residues 1–60), where most disease-causing familial mutations are located and which binds to membranes; (ii) a hydrophobic nonamyloid-β component (NAC) region (residues 61–95) that is thought to be the core region for aggregation; and (iii) a disordered negatively charged C-terminal region (residues 96–140). Both N- and C-terminal regions can affect α-synuclein aggregation and fibril propagation. While the negatively charged C-terminal region plays a crucial role in suppressing α-synuclein aggregation, N-terminal residues are essential for fibril formation. , A helix-rich model of the α-synuclein monomer structure has been resolved by solution NMR in the micellar environment and is deposited in the Protein Data Bank (PDB) under PDB ID: 1XQ8 . Using molecular dynamics simulations we study how SK9 interacts with α-synuclein and whether SK9 changes the conformational ensemble of the monomer, potentially modifying oligomerization and hastening the formation of a critical nucleus for seeding fibrils.…”
Section: Introductionmentioning
confidence: 99%
“…The computed α-Syn monomer dynamics shows the formation of α-helices in the N-terminus with a β-hairpin formed close to the NAC region. Recent studies on monomers and dimers have indicated that α-Syn samples a heterogeneous ensemble of interconverting conformations in an aqueous solution, including parallel and antiparallel β-sheets and transient α-helical conformations, , with long stretches of α-helices predicted to impede pathogenic aggregation of α-Syn. However, compared to α-Syn in bulk water, the reduced conformational freedom of α-Syn at the gold–water interface may stabilize fibril-like morphologies, as also noted previously for adsorption of amyloid-β-42 peptide on gold and amyloid-β-42 protofibrils on graphene . For the Cu 2+ /monomer (1:1) complex, the maximum height is ∼3.4 nm with a narrow distribution showing that the high affinity of Cu 2+ for NT compacts the monomer (Figure b) via additional Cu 2+ –CT interactions (Figure S12a ) and is close to the maximum height of spherical particles when exposed to 1 μM Cu 2+ obtained from our AFM experiments (∼3.25 nm) (see Figure c, red histogram).…”
Section: Resultsmentioning
confidence: 71%
“…Previously, we have shown that a Sirtuin ligand, SirReal2, is particularly effective in inducing a structural rearrangement of the active site that exposes an adjacent binding pocket and that results in hyperacetylation of the microtubule network (Figure 3) [62]. Allosteric regulation has been reported for PPIs involving SYN, which is based on targeting SYN outside the interface [63]. In fact, the inter-domain coupling suggests a form of intra-molecular allosteric regulation of the aggregation trigger in the partially folded helical monomers (Figure 4).…”
Section: Allosteric Regulationmentioning
confidence: 95%